2009
DOI: 10.1158/0008-5472.can-09-0596
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Infection and Gastric Cancer Risk: Evaluation of 15 H. pylori Proteins Determined by Novel Multiplex Serology

Abstract: Infection with Helicobacter pylori is a major cause of gastric cancer (GC). The association likely has been underestimated in the past due to disease-related clearance of the infection. On the other hand, only a minority of the infected individuals develop GC, and better risk stratification is therefore highly desirable. We aimed to assess the association of GC with antibodies to 15 individual H. pylori proteins, determined by novel multiplex serology, to identify potentially relevant risk markers. This analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
91
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 76 publications
(103 citation statements)
references
References 38 publications
9
91
3
Order By: Relevance
“…Also, it has been shown in different studies that these two antigens are found more often in patients with gastrointestinal disorders (23). These findings make GroEL and HcpC interesting for serological testing, as they show good immune responses in infected patients.…”
Section: Specific and Sensitive H Pylori Line Immunoassaymentioning
confidence: 88%
“…Also, it has been shown in different studies that these two antigens are found more often in patients with gastrointestinal disorders (23). These findings make GroEL and HcpC interesting for serological testing, as they show good immune responses in infected patients.…”
Section: Specific and Sensitive H Pylori Line Immunoassaymentioning
confidence: 88%
“…The state of Saarland was chosen, inter alia, as highly efficient, and reliable long-term follow-up of patients with cancer is possible through the Saarland Cancer Registry (12). In the ESTHER II study more than 2,000 patients of ages 50 to 74 years and diagnosed with various forms of cancer were recruited between January 2001 and December 2003 (13); in the VERDI study 908 patients of ages 80 years or less with a first diagnosis of breast, colorectal, or gastric cancer were recruited between October 1996 and February 1998 (14).…”
Section: Study Populationmentioning
confidence: 99%
“…Details of both studies have been reported elsewhere (13)(14)(15). In the VERDI study exact ascertainment of participation rates of patients with breast cancer approached by their physician was possible, and participation was found to be very high (387 of 401 eligible women, 96.5%).…”
Section: Study Populationmentioning
confidence: 99%
“…For example, determining immunological fingerprints to clarify the role of past infections in lymphomagenesis may employ technologies such as multiplex serology (e.g., Luminex ® technology) in large-scale epidemiological studies. Recently, data on 15 H. pylori proteins in the context of chronic atrophic gastritis and gastric cancer risk were published [64,65], and similar approaches may improve internal exposure assessment for NHL and facilitate gene-environment ana lysis in H. pylori-associated MALT lymphoma. Detailed phenotyping of NHL subtypes that incorporate genetic, epigenetic and other molecular data may also improve the detection of potential interactions.…”
Section: Five-year Viewmentioning
confidence: 99%